Green approach towards size controlled synthesis of biocompatible antibacterial metal nanoparticles in aqueous phase using lysozyme - Kumar, Umesh; Ranjan, Amaresh K.; Sharan, Chandrashekhar; Hardikar, Anandwardhan A.; Pundle, Archana; Poddar, Pankaj (Current Nanoscience, 2012)
Inspired by array of proteins present in nature, we choose lysozyme (hen egg protein) as a model system to synthesize nanoparticles of noble metals to understand the mechanism of interaction as well as to use them for potential applications such as potent antibacterial agents. Lysozyme is a very well studied biomolecule containing aromatic amino acids like tryptophan and tyrosine. Tyrosine has phenoxy group which is considered to be responsible for interacting with the metal ions. Lysozyme can be suitably modified by treatment with N-bromosuccinimide/N-acetylimidazole to obtain tight control over size distribution of nanoparticles. Here we report the direct synthesis of nanocrystals of gold and silver at controlled pH and light conditions without using any known reducing agents. Out of these, synthesis of gold nanoparticles is assisted by the presence of low concentration of Ag+ ions through the galvanic exchange. It is remarkable to note that the structure of protein is not changed drastically as seen by the FTIR studies. As-synthesized lysozyme capped nanoparticles prepared by this method are biocompatible and retain antibacterial property.
Keywords: Antibacterial; Biocompatible; Gold; lysozyme; Nanoparticles; Silver

Novel route for rapid biosynthesis of copper nanoparticles using aqueous extract of Calotropis procera L. latex and their cytotoxicity on tumor cells - Harne, Shrikant; Sharma, Ashwinikumar; Dhaygude, Mayur; Joglekar, Shriram; Kodam, Kisan M.; Hudlikar, Manish (Colloids and Surfaces B-Biointerfaces, 2012)
This paper accounts for novel, low-cost, eco-friendly route for rapid biosynthesis of copper nanoparticles. Cysteine proteases present in the latex of Calotropis procera L. were used to fabricate copper nanoparticles from copper acetate. Copper nanoparticles were initially characterized by transmission electron microscopy (TEM) and X-ray diffraction technique (XRD). Transmission electron microscopy (TEM) was used to estimate the size and shape of nanoparticles. The average size of copper nanoparticles was found to be 15 +/- 1.7 nm. Energy dispersive analysis of X-rays (EDAX) showed distinct peaks of copper. Fourier transform infrared spectroscopy (FTIR) was performed to confirm capping behavior of the latex proteins that contributed to long term stability of copper nanoparticles (6 months) in aqueous medium. Copper nanoparticles synthesized by above method were monodisperse type. Cytotoxicity studies of latex stabilized copper nanoparticles were carried out on HeLa, A549 and BHK21 cell lines by MTT dye conversion assay. HeLa, A549 and BHK21 cells showed excellent viability even at 120 mu M concentration of copper nanoparticles. This shows that copper nanoparticles synthesized by above method hold excellent biocompatibility. (C) 2012 Elsevier B.V. All rights reserved.
Keywords: Biocompatible; Copper nanoparticles; FTIR; Latex; Tumor cells; X-ray diffraction technique (XRD)

Fluorescent cadmium telluride quantum dots embedded chitosan nanoparticles: a stable, biocompatible preparation for bio-imaging - Ghormade, Vandana; Gholap, Haribhau; Kale, Sonia; Kulkarni, Vaishnavi; Bhat, Suresh; Paknikar, Kishore (Journal of Biomaterials Science-Polymer Edition, 2015)
Fluorescent cadmium telluride quantum dots (CdTe QDs) are an optically attractive option for bioimaging, but are known to display high cytotoxicity. Nanoparticles synthesized from chitosan, a natural biopolymer of beta 1-4 linked glucosamine, display good biocompatibility and cellular uptake. A facile, green synthetic strategy has been developed to embed green fluorescent cadmium telluride quantum dots (CdTe QDs) in biocompatible CNPs to obtain a safer preparation than `as is' QDs. High-resolution transmission electron microscopy showed the crystal lattice corresponding to CdTe QDs embedded in CNPs while thermogravimetry confirmed their polymeric composition. Electrostatic interactions between thiol-capped QDs (4nm, -57mV) and CNPs (\~300nm, +38mV) generated CdTe QDs-embedded CNPs that were stable up to three months. Further, viability of NIH3T3 mouse fibroblast cells in vitro increased in presence of QDs-embedded CNPs as compared to bare QDs. At the highest concentration (10 mu g/ml), the former shows 34 and 39% increase in viability at 24 and 48h, respectively, as compared to the latter. This shows that chitosan nanoparticles do not release the QDs up to 48h and do not cause extended toxicity. Furthermore, hydrolytic enzymes such as lysozyme and chitinase did not degrade chitosan nanoparticles. Moreover, QDs-embedded CNPs show enhanced internalization in NIH3T3 cells as compared to bare QDs. This method offers ease of synthesis and handling of stable, luminescent, biocompatible CdTe QDs-embedded CNPs with a favorable toxicity profile and better cellular uptake with potential for bioimaging and targeted detection of cellular components.
Keywords: Biocompatible; bioimaging; CdTe quantum dots; chitosan nanoparticles; Toxicity

Polylactic acid: synthesis and biomedical applications - Singhvi, M. S.; Zinjarde, S. S.; Gokhale, D. V. (Journal of Applied Microbiology, 2019)
Social and economic development has driven considerable scientific and engineering efforts on the discovery, development and utilization of polymers. Polylactic acid (PLA) is one of the most promising biopolymers as it can be produced from nontoxic renewable feedstock. PLA has emerged as an important polymeric material for biomedical applications on account of its properties such as biocompatibility, biodegradability, mechanical strength and process ability. Lactic acid (LA) can be obtained by fermentation of sugars derived from renewable resources such as corn and sugarcane. PLA is thus an eco-friendly nontoxic polymer with features that permit use in the human body. Although PLA has a wide spectrum of applications, there are certain limitations such as slow degradation rate, hydrophobicity and low impact toughness associated with its use. Blending PLA with other polymers offers convenient options to improve associated properties or to generate novel PLA polymers/blends for target applications. A variety of PLA blends have been explored for various biomedical applications such as drug delivery, implants, sutures and tissue engineering. PLA and their copolymers are becoming widely used in tissue engineering for function restoration of impaired tissues due to their excellent biocompatibility and mechanical properties. The relationship between PLA material properties, manufacturing processes and development of products with desirable characteristics is described in this article. LA production, PLA synthesis and their applications in the biomedical field are also discussed.
Keywords: Biocompatible; biodegradable; drug delivery; implants; l- and d-lactic acid; polylactic acid

Magnetic and luminescent multifunctional nanohybrid: Fe3O4@CaF2:Tb3+: a facile synthesis and characterization - Vats, Monika; Kumar, Rakesh; Sharma, Jyotsna; Luwang, Meitram Niraj (Indian Journal of Pure & Applied Physics, 2020)
In the present study, bi-functional hybrid nanomaterial has been synthesized and characterized via facile method and characterized. The synthesized nanomaterial shows both magnetic and luminescent properties which are confirmed by VSM (vibrating sample magnetometer), UV-Vis spectra and the photoluminescence emission spectra. For the magnetic phase, i.e., nanocrystalline magnetite, Fe3O4 is used as the core which is then functionalized using polyethylene glycol (PEG) and for the luminescent phase, polyethylenimine (PEI) functionalized CaF2 doped with Tb3+ is used as the emitter. Wherein, both PEG and PEI serve the dual purpose of functionalization as well as stabilization by steric repulsion. The structure and morphology of the synthesized bifunctional hybrid nanomaterial are studied with the help of scanning electron microscopy (SEM) and X-ray powder diffraction.
Keywords: Biocompatible; CaF2; Co-precipitation; Fe3O4; Luminescent nanoparticle; Magnetic nanoparticles; Nanohybrid; Tb3+ doping

Synthesis and characterization of biocompatible poly (L-lactide) using zinc (II) salen complex - Rade, Priyanka P.; Garnaik, Baijayantimala (International Journal of Polymer Analysis and Characterization, 2020)
A biocompatible zinc (II) complex based on a tetradentate N,N,O,O-type salen ligand was synthesized, characterized and used for the solvent-free ring-opening polymerization (ROP) of L-lactide in bulk at 180 degrees C to prepare high molecular weight poly(L-lactide) (M-n: 82,600 Da;M-w: 140,000 Da; PDI: 1.70). Poly(L-lactide) (PLLA) was characterized using FTIR,H-1 NMR,C-13 NMR, GPC, TGA, DSC, WAXD, and MALDI-ToF. Kinetic measurement was carried out and first-order behavior to monomer was observed. Thek(app)was found as 6 +/- 0.001 x 10(-4 )s(-1). The biocompatibility of the PLLA was confirmed byin vitrocytotoxicity against NIH/3T3 fibroblast cell line and can be used in biomedical applications.
Keywords: Biocompatible; Biomedical Applications; in vitro; PLLA; zinc (II) salen complex